Optimization of Machining Parameters and Nano-Lubricant Effects on Drilling, Grinding, and Turning Machining Process; Challenges and Future Trends - A Review - Omoniyi, P. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Any machining operation that generates heat must adequately dissipate it to minimize thermal stresses on the tool-workpiece contact. This inescapable heat production phenomenon, caused by using suboptimal machining parameters and a lack of long-lasting machining lubricant, adversely impacts the finished surface quality, tool destruction rate, and workpiece structure. Therefore, this review focuses on optimizing machining parameters and nano-lubricant effects on the various response parameters such as surface finishing, materials removal rate, tool wear rate, and cutting forces under drilling, grinding, and turning machining. The study reviewed reputable articles from Elsevier, Springer, and other quality outlets. This review cut across the impact of machining parameters and nano-lubricants on the drilling, grinding and turning process. The study also discussed the challenges of optimizing machining parameters during the drilling, grinding, and turning.